Sistem Informasi Petir (SIP) Dengan Metode Lightning Distribution (LD) di Wilayah Sumatera Barat - Andrew Kurniawan Vadreas; Primas Emeraldi; Ariadi Hazmi (Jurusan Teknik Elektro Universitas Andalas, 2014)
This paper mapped 200 locations of lightning strikes in West Sumatra province. Mapping the location of lightning strikes as part of Lightning Information System was designed with the method of Lightning Distribution (LD). To get the location of lightning strikes obtained from the calculation reflection of ionosphere method to determine the distance of a lightning strike from stations of lightning and methods of Magnetic Direction Finding (MDF) to get directions from the lightning strike. Direction data obtained processed to generate a lightning incident location, then that location will be displayed on Google Maps. After that in the process of Lightning Distribution method which is a form of lightning strike density mapping by using the